Contando história: a superação de uma situação traumática por meio da criatividade - Michaan, Léa (2012)
In the present work, I tell the story known as "O Contador de Historias", which discusses the case of a boy who suffered trauma through abrupt ruptures that interrupted the flow of good experiences in the course of his maturation process. Besides losing significant experiences that facilitate life, the boy is also subjected to complex situations that demand more mental resources than he possess at the specific point of his maturation. The traumatic aspects of this narrative are the unexpected outcomes in the life of someone suffering from deprivation characterized by sudden disruptions in the natural course of life and the need to deal with situations that require more mental resources than the ones available. The aim of this paper is to unveil the creative resources that a person can use in face of this model of trauma. According to Winnicott, every human being has creative potential and we can observe that the boy in the story studied has creativity as primary anthropological model. Also, according to the same author, creativity is never destroyed or lost. In the story studied, we see that the creativity of the child updates itself in three different situations: At first, in face of the defensive organization of the antisocial tendency displayed by the boy as an attempt to create a mental scape from the pain inflicted by the intrusive/invasive environment; Secondly, through the way the boy search, go for and test the reliability of the significant person with whom he can update his creativity and direct it to the potential field so that, from that moment on, the boy could give cultural destinations to his creative potential. Finally, we observe how the boy develops ownership over his creative potential, causing his creativity to emerge with great power. Creativity is presented in this study as a source for resilience and possibility to achieve our goals